NEURITIS OPTIK SIFILIS PADA PASIEN IMUNOKOMPETEN - Ni Nyoman Mestri Agustini,* Ida Ayu Sri Indrayani,* Ni Made Susilawathi,* Dewa Putu Gede Purwa Samat (Neurona Majalah Kedokteran Neuro Sains, 2017)
OPTICS SYPHILIS IS A NEUROOPHTHALMOLOGY MANIFESTATION WHICH OCCUR IN LATENT PHASE SYPHILIS SYPHILIS IS A SEXUALLY TRANSMITTED DISEASE AND NOWADAYS THE INCIDENCE IS INCREASING IN IMMUNOCOMPROMISE PATIENTS SPECIALLY IN HIV AIDS INFECTION NEVERTHELESS THE OCCURRENCE IN IMMUNOCOMPETENT PERSON IS VERY RARE ONLY 0221 CASES IN 100000 PEO PLE DISORDERS OF THE EYE ARE ALSO NOT COMMON AND USUALLY ASYMPTOMATIC OPTICS NERVE INVOLVEMENT MAY BE UNILATERAL OR BILATERAL WITH MANIFESTATION AS PERINEURITIS ANTERIOR OPTICS AND RETRO BULBAR NEURITIS OR PAPILLEDEMA